Parceria público-privada: uma proposta para a gestão do Parque do Goiabal em Ituiutaba, Minas Gerais - Brasil - Moraes, Dario Junqueira de (2023)
Parque do Goiabal is an urban green park in the city of Ituiutaba, Minas Gerais, and has been closed for over thirty years due to political and budgetary reasons. The community of Ituiutaba urgently needs the park to be reopened for public visitation. In this context, the present work was conducted with the aim of proposing, as an alternative, a Public-Private Partnership for the management of the park and assessing its feasibility. With this in mind, a literature review was conducted on the legislation related to the subject, presenting some concrete cases where this type of investment has been made. To assess the real viability of this initiative in the city, interviews were conducted with representatives from the community, both from the public and private sectors, to understand their opinions and interests in this mechanism. Additionally, a virtual survey was carried out to gauge public opinion on the matter from a purely qualitative perspective. The results of the study were positive, as it was possible to verify, through interviews with representatives from the public executive and legislative branches, as well as with representatives from the private sector, that the establishment of a Public-Private Partnership for the management of the Parque do Goiabal in Ituiutaba could be feasible. This is because the municipal administration lacks the financial means to adequately guard and protect this public green area, and with the assistance of the private sector, it could effectively carry out the public service it is tasked with providing.